Application of the Wordwall Application in Social Studies Learning to Develop Independent Character in Elementary School Students - Sufraini, Sufraini; Prastowo, Andi; Budi, Tegar Setia (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
Student independence in elementary schools is still considered low because many students rely on teachers to learn and more brilliant friends to work on questions. The culture of cheating when working on exam questions reflects that students lack confidence in their abilities. This study aims to provide an overview of using the Wordwall application as a learning medium for Natural and Social Sciences (IPAS) in developing the independent character of elementary school students. The researcher used a descriptive qualitative research method with data from interviews, observations, and documentation. This study found that the Wordwall application increased student engagement through interactive features that motivated and enriched the learning experience. Wordwall also supported students' self-directed learning by providing instant feedback, allowing them to explore and understand concepts independently. This application helped develop learning discipline and critical thinking skills through trial-and-error mechanisms. For optimization, Wordwall should be combined with other learning methods and integrated into a broader pedagogical approach to support the internalization of independent and disciplined characters in students' lives. The contribution of this study is to show the effectiveness of the Wordwall application in increasing student engagement and self-directed learning through its interactive features. This study recommends the integration of Wordwall with other learning methods to support the development of students' discipline and critical thinking skills more effectively.